2020
DOI: 10.1186/s12935-020-01285-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The novel long non-coding RNA LATS2-AS1-001 inhibits gastric cancer progression by regulating the LATS2/YAP1 signaling pathway via binding to EZH2

Abstract: Background: To explore the expression pattern and role of the novel long non-coding RNA LATS2 antisense transcript 1 (LATS2-AS1-001) in gastric cancer (GC). Methods: qRT-PCR was applied to evaluate LATS2-AS1-001 expression and correlation with LATS2 in GC. In vitro experiments were performed to investigate the role of LATS2-AS1-001 in GC cells. RNA immunoprecipitation (RIP) was performed to assess the interaction between EZH2 and LATS2-AS1-001. LATS2/YAP1 signaling pathway proteins were detected by immunoblot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The results demonstrated that YAP1 and TEAD1 were highly expressed in osteosarcoma cells and tissues, especially in Saos-2 cells. Consistently, previous studies have demonstrated that YAP1 is implicated in tumorigenesis, facilitating the progression of a number of types of cancer including gastric, liver and peritoneal cancer ( 24 26 ), whereas TEAD1 expression is upregulated in various types tumor such as medulloblastoma, renal and gastric cancer, suggesting a tumor-promoting role for TEADs ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 83%
“…The results demonstrated that YAP1 and TEAD1 were highly expressed in osteosarcoma cells and tissues, especially in Saos-2 cells. Consistently, previous studies have demonstrated that YAP1 is implicated in tumorigenesis, facilitating the progression of a number of types of cancer including gastric, liver and peritoneal cancer ( 24 26 ), whereas TEAD1 expression is upregulated in various types tumor such as medulloblastoma, renal and gastric cancer, suggesting a tumor-promoting role for TEADs ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, the miR-93-5p inhibitor expedited the Hippo pathway in HP + GC cells by elevating LATS2 protein expression [29]. Mechanistically, overexpression of LATS2-AS1-001 has been indicated to induce LATS2 and YAP1 phosphorylation via binding to EZH2 [30]. Still, the detailed mechanism behind the LATS2-mediated Hippo pathway in GC awaits further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling studies have observed that lncRNAs participate in many cell biological processes, including carcinogenesis and development [ 32 – 34 ]. For instance, Sun et al [ 35 ]. proved that lncRNA LATS2-AS1-001 suppressed GC development by modulating the YAP1/LATS2 pathway by binding to EZH2.…”
Section: Discussionmentioning
confidence: 99%